Dental anomalies in the deciduous dentition of non-syndromic oral clefts patients - Adriana Boeri Freire Tamburini; Ygor Henrique Pereira Rodrigues; Daniella Reis Barbosa Martelli; Letízia Monteiro de Barros; Rodrigo Soares de Andrade; Renato Assis Machado; Ricardo Della Coletta; Hercílio Martelli-Júnior; Flávia Martão Flório (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to investigate the prevalence of dental anomalies in complete deciduous dentition of children with NSCL/P. Methods: this study included 75 children with NSCL/P and 286 healthy control. In both groups the children had deciduous dentition with ages varying from 4 to 6 years. Clinical examination, panoramic and periapical radiographies were performed and dental anomalies of number and shape were considered. Results: there was a higher prevalence of dental anomalies in the case group, compared to the control group. In all, 42 dental anomalies were identified, 25.33% in the case group and 8.04% in control group (p<0.001). Therewas a higher frequency of dental anomalies in NSCL/P (47.36%), followed by non-syndromic cleft lip (31.57%) and non-syndromic cleft palate (21.05%). The occurrence of agenesis (p= 0.005) and twinning (p = 0.029) were higher in the case group. Conclusions: the occurrence of agenesis and dental twinning was more frequent in the case group and may contribute to the definition of oral cleft subphenotype.